The T-loop extension of the tomato protein Kinase AvrPto-dependent Pto-interacting Protein 3 (Adi3) directs nuclear localization for suppression of plant cell death - Ek Ramos, María Julissa; Avila, Julian; Cheng, Cheng; Martin, Gregory B.; Devarenne, Timothy P. (2010)
In tomato (Solanum lycopersicum), resistance to Pseudomonas syringae pv. tomatois elicited by the interaction of the host Pto kinase with the pathogen effector protein AvrPto, which leads to various immune responses including localized cell death termed the hypersensitive response. The AGC kinase Adi3 functions to suppress host cell death and interacts with Pto only in the presence of AvrPto. The cell death suppression (CDS) activity of Adi3 requires phosphorylation by 3-phosphoinositide-dependent protein kinase 1 (Pdk1) and loss of Adi3 function is associated with the hypersensitive response cell death initiated by the Pto/AvrPto interaction. Here we studied the relationship between Adi3 cellular localization and its CDS activity. Adi3 is a nuclear-localized protein, and this localization is dictated by a nuclear localization signal found in the Adi3 T-loop extension, an ∼80 amino acid insertion into the T-loop, or activation loop, which is phosphorylated for kinase activation. Nuclear localization of Adi3 is required for its CDS activity and loss of nuclear localization causes elimination of Adi3 CDS activity and induction of cell death. This nuclear localization of Adi3 is dependent on Ser-539 phosphorylation by Pdk1 and non-nuclear Adi3 is found in punctate structures throughout the cell. Our data support a model in which Pdk1 phosphorylation of Adi3 directs nuclear localization for CDS and that disruption of Adi3 nuclear localization may be a mechanism for induction of cell death such as that during the Pto/AvrPto interaction.